Discernible impact of augmented reality on retail customer's experience, satisfaction and willingness to buy. (January 2017) - Poushneh, Atieh; Vasquez-Parraga, Arturo Z.
Abstract: User technology has an agreeable impact on consumer decisions; yet the way such impact takes place may be little known. This study attempts to examine the impact of augmented reality (AR) on retail user experience (UX) and its subsequent influence on user satisfaction and user's willingness to buy. Five hypotheses are tested using a lab experiment. The results show that AR significantly shapes UX, by impinging on various characteristics of product quality, and that UX subsequently influences user satisfaction and user's willingness to buy. UX is captured as a third-order formative construct derived from four user experience characteristics: pragmatic quality, aesthetic quality, hedonic quality by stimulation and hedonic quality by identification. Except for the latter, these characteristics are second-order constructs. Important implications for researchers and managers follow.